Audiência de custódia no Brasil e os desafios de sua implantação - Gonçalves, Fernando David de Melo (2017)
The purpose of this paper is to analyze the theme of the custody hearings with a focus on the challenges for its effective implementation in Brazil. In order to do so, the evolution of human rights, especially freedom, physical integrity and life, in face of state arbitrariness, was first tackled, until the phase of international law that conceived standards of protection of the same rights was adopted. The period of world wars was highlighted as a determining factor in the uprising of the brakes on the power of nation-states. Thus, the era of Humanitarian Law was reached, culminating, among others, in the International Covenant on Civil and Political Rights, and especially in the American Convention on Human Rights, also known as the Pact of St. Joseph of Costa Rica. The latter two, and other treaties, expressly contemplated the custody hearing with faint prediction differentiations, which were punctuated and discussed. Next, the structural characteristics of the custody‟s hearing, more precisely definition, legal nature, principles, purposes, fences and the meaning of the term "without delay" were discussed. In that detail, it was recalled that Brazil already provided for the control of procedural caution and a mechanism to curb any abuse in the act of capture, namely, the conversion of mere detention into custody in flagrante delicto, a task of a jurisdictional nature delegated to the police authority since ancient times in Brazilian legal history. After that, the challenges overcome were overcome in the arduous task of making the custody hearings possible in the country. Therefore, the beginning of the activities of the so-called "Custody Hearings" project, launched on February 6, 2015, was initiated, based on an agreement involving, at the federal level, the National Justice Council and the Ministry of Justice and, at the state level of São Paulo, Public Ministry, Court of Justice, State Government, Public Defender and OAB. The project was successful, achieving full installation on October 14, 2015, with the signing of the respective endorsement by the District Court of Brasilia. Finally, statistical data related to the custodial audience, mostly quantitative imbricated to the cost of the provisional prison for the Brazilian´s penitentiary system, were collationed in order to try to prove its economic-financial sustainability and to qualify this eminent public policy as an inexorable and salutary fact to the Development of criminal justice.